Mechanism of action of Bu Zhong Yi Qi Decoction in the treatment of chronic fatigue syndrome based on network pharmacology and molecular docking - Jie Zhang; Xiaoju Liu; Xin Li; Zhenhao Ying; Wei Liu (Elsevier, 2022)
Objective: Bu Zhong Yi Qi (BZYQ) decoction is a classic prescription in Chinese history that has an obvious effect on improving fatigue symptoms. The objective was to investigate the substance basis and mechanism of BZYQ in the treatment of chronic fatigue syndrome (CFS) at the molecular level based on network pharmacology and molecular docking technology. Method: The active components and their targets of Huangqi, Baizhu, Renshen, Gancao, Danggui, Chaihu, Chenpi, Shenma in BZYQ were screened by the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) database and the Encyclopedia of Traditional Chinese Medicine (ETCM). The UniProt database was used to calibrate the target information in BZYQ. CFS target genes were obtained from the GeneCards and DisGeNET databases. Cytoscape 3.7.2 software and the STRING 11.0 database were used to construct a protein-protein interaction (PPI) network and screen core targets. Then, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed using the Database for Annotation, Visualization and Integrated Discovery (DAVID) database. Subsequently, the binding affinity of BZYQ with key target receptors was assessed by molecular docking analysis. Result: BZYQ consists of 329 active components, 198 targets, and 6490 CFS-related targets. There were 180 common targets of BZYQ and CFS, including nitric oxide synthase Ⅱ (NOS2), estrogen receptor beta (ESR2), interleukin-2 (IL2), interleukin-6 (IL6), interleukin-1 beta (IL1B), MAP kinase-activated protein kinase 3 (MAPK3), vascular endothelial growth factor A (VEGFA), nitric oxide synthase Ⅲ (NOS3), and matrix metallopeptidase 2 (MMP2). More than 600 GO terms were obtained (Biological Process 630; Cellular Component: 95; Molecular Function:152) and 185 related signaling pathways, involving the AGE-RAGE signaling pathway in diabetic complications, pathways in cancer, TNF signaling pathway, lipid and atherosclerosis, cAMP signaling pathway, VEGF signaling pathway, calcium signaling pathway, and NF-kappa B signaling pathway. Conclusion: BZYQ achieves the purpose of treating CFS through the interaction mechanism of multiple components, multiple targets and multiple pathways. It advances the study of BZYQ to the clinical stage, expounds the effective mechanism of Traditional Chinese Medicine from an overall perspective, and provides ideas at the molecular level for future experimental study.